Proteolysis Targeting Chimeras (PROTACs) Based on Promiscuous Kinase Inhibitor Synergistically Induce Cancer Cell Apoptosis Through Multiple Mechanisms. Issue 40 (25th October 2022) - Zhai, Jiadai; Li, Chuang; Wang, Sinan; Sun, Bingxia; Cui, Yuting; Gao, Qingzhi; Sang, Feng
Abstract: Eleven new proteolysis targeting chimeras (PROTACs) based on promiscuous kinase inhibitor Sunitinib were designed, synthesized, and assessed for their anticancer activity against four human cancer cell lines A498, K562, HL‐60 and MCF‐7. Two known compounds were also prepared and used as control samples. The CCK‐8 assay results showed that a new PROTAC with a 1, 4‐diaminobutane linker (PROTAC 10 ) exhibited significant antiproliferative activity against A498 (IC50 =0.11 ± 0.01 μM) and K562 (IC50 =0.59 ± 0.21 μM) cell lines. Western blot analysis showed that in addition to the previously reported G1 to S phase transition 1 (GSPT1), PROTAC 10 also reduced the protein level of fms‐like tyrosine kinase 3 (FLT3) and proto‐oncogene tyrosine protein kinase Src (SRC) in A498 cells. Moreover, PROTAC 10 regulated the protein levels of GSPT1 and SRC in a dose‐ and time‐dependent manner and induced degradation of GSPT1 in a ubiquitin‐proteasome‐dependent manner in K562 cells. Abstract : A new series of Proteolysis Targeting Chimeras (PROTACs) based on Sunitinib and Thalidomide have been designed, synthesized, and evaluated for their antiproliferative activity against four human cancer cell lines. A new PROTAC with a 1, 4‐diaminobutane linker exhibited significant activity against A498 and K562 cells. Western blot results showed that the new PROTAC reduced the levels of multiple proteins through different pathways.